Metabolism of six CYP probe substrates in fetal hepatocytes - Abdul Naveed Shaik; Sandeep Kumar Vishwakarma; Aleem A Khan (International Association of Physical Chemists (IAPC), 2016)
Cytochrome P-450 (CYP) are the most common drug metabolizing enzymes and are abundantly expressed in liver apart from kidney, lungs, intestine, brain etc. Their expression levels change with physiological conditions and disease states. The expression of these CYPs is less in human foetus and neonates compared to adults, which results in lower clearance of xenobiotics in infants and neonates compared to adults. Hepatocytes are the cells which are largely used to study these CYPs. We have isolated hepatocytes from aborted foetus to study the metabolism of six probe substrates: phenacetin, diclofenac, S-mephenytoin, dextromethorphan, nifedipine and testosterone. The results obtained show the expression of various CYPs (CYP1A2, CYP2C19, CYP2C9, CYP2D6, and CYP3A4) in human foetus and their involvement in metabolism of CYP probe substrates.